A study on the argumentativeness of the management team members of Davao del Norte State College - Nemenzo, Arianne S.
The study in argumentativeness of the Management Team members was conducted in order to better understand the communication behaviors of the Management Team members in an argument, which arose during the group discussion on matters related to their decision-making task. The study is grounded to trait theory's assumption that communication behaviors are influenced by communication traits and to the notion that decision quality is affected by the input and output factors that the group members contribute. The study generally aims to know how argumentative the Management Team members are and particularly aims to determine the members' levels of argumentativeness, motivations to approach and avoid argument, perceptions on argument and argumentativeness, communication behaviors, and factors that affect communication behaviors. The study is based on the Management Team members' self-supported data gatheres through quantitative and qualitative research methods: Infante and Rancer's Argumentativeness Scale and interview, respectively. The quantitative data were analyzed based on the Argumentativeness Scale's item statements and formula ARGgt = (ARGap + 60) ? ARGav. The interview data were analyzed through content analysis. Results of the study show that the Management Team members are moderate argumentatives with motivational tendencies to approach and avoid argument. Argument was perceived as a means to achieve task goals, as well as a normal occurrence and important part of group decision-making, argumentativeness was perceived as a positive communication trait given that certain conditions should be met. Argumentative communication behaviors, which are perceived to be influenced by both dispositional and situational factors, were exhibited during argument. The first implication of the study is that Management Team is capable of coming up with high quality decisions, and its members are interpersonally skilled and adaptable individuals. Second, argumentativeness does not necessarily determine communication behaviors, but it influences the perceptions and decisions of individuals whether to approach or avoid argument. Lastly, there is a need to enhance argumentativeness in order to have a productive group and high quality group decisions.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication